2001
DOI: 10.1021/bi002210u
|View full text |Cite
|
Sign up to set email alerts
|

Probing of Metal-Binding Domains of RNA Hairpin Loops by Laser-Induced Lanthanide(III) Luminescence

Abstract: Direct laser excitation of aqueous Eu(III) bound to specific RNA fragments was used to probe the metal-binding sites of the anticodon loop of tRNA(Phe) from E. coli and of a tetraloop containing a GNRA consensus sequence. Binding of Mg(II) or Eu(III) to either RNA fragment resulted in a higher melting transition, but no global change in structure was observed. Aqueous Eu(III) exhibits a single weak excitation peak at 17273 cm(-1), the intensity of which increased upon addition of the tRNA loop fragment. Analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(51 citation statements)
references
References 63 publications
3
47
1
Order By: Relevance
“…[40] Lanthanide ions were used as effective cofactors for a Pb II -dependent DNAzyme to probe metal-binding sites, [50] and luminescence lifetime experiments were used to find the number of coordinated waters on the lanthanide ions binding to the hammerhead ribozyme [39] and RNA hairpin loops. [51] In this study, we report that Tb III Figure 1A. Previous studies had shown that a single base change-T2.1C-producing a GC base pair instead of the GT wobble pair adjacent to the cleavage site abolished the metal-dependent activity.…”
Section: Introductionsupporting
confidence: 49%
“…[40] Lanthanide ions were used as effective cofactors for a Pb II -dependent DNAzyme to probe metal-binding sites, [50] and luminescence lifetime experiments were used to find the number of coordinated waters on the lanthanide ions binding to the hammerhead ribozyme [39] and RNA hairpin loops. [51] In this study, we report that Tb III Figure 1A. Previous studies had shown that a single base change-T2.1C-producing a GC base pair instead of the GT wobble pair adjacent to the cleavage site abolished the metal-dependent activity.…”
Section: Introductionsupporting
confidence: 49%
“…Clearly, Eu 3+ or Tb 3+ can destabilize It should be noted that the destabilization effect on GTT 3 -7AACTD complex is stronger than GAA 3 -7AACTD complex at the same binding ratio (Table 1), and Eu 3+ has even stronger effect than Tb 3+ . This is different from a previous report [9] that Eu 3+ can stabilize DNA hairpin structure [9]. The difference can be caused by the different route for hairpin formation.…”
Section: Resultscontrasting
confidence: 98%
“…The DNA used in Ref. [9] is a naturally formed hairpin DNA. However, the DNA we used cannot form hairpin structure by itself under our experimental conditions, the hairpin structure is induced upon 7AACTD binding.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Concentration was measured by titration with EDTA as described previously (19). The excitation wavelength was 280 nm.…”
Section: Methodsmentioning
confidence: 99%